Identification Of Rhodamin B Syntethic Dye On School Children Snacks In Peguyangan Kangin Village City Of Denpasar - Luh Amla Suwerni; I Gusti Putu Sudita Puryana; Badrut Tamam (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2021)
School children's snacks are food or drinks that have been processed in such a way that can be directly served to consumers especially for schoolchildren who are outside the school cafeteria. Adding dye to food is done for some purpose, which gives the impression of attracting attention to consumers. School children's snacks are a very concern for people, especially parents and teachers, because this food is very risky against chemical contamination or its toxication, so it can have a bad impact on the health of short term natural d. Especially chemical contamination often misused is the synthetic dye Rhodamin B. Rhodamin B is a synthetic dye of red or pink color givers that are usually used for textiles and paper so it is dangerous when consumed. The use of Rhodamin B in prolonged (chronic) food will result in impaired liver function and cancer. The purpose of this research is to identify whether it contains the dye Rhodhamin B in the school children's food in Peguyangan Kangin village Denpasar city. The study uses a descriptive observational without giving intervention. Samples are taken in purposive sampling. Number of samples as many as 12 children's snacks namely macaroni, sugar ice, cilok sauce, sempol sauce, wax ice, doger ice, jelly candy, pop corn, cassava balls, and bijik. Identification of Rhodamin B synthetic dyes in children's snacks were tested in the laboratory department of Nutrition Poltekkes Kemenkes Denpasar by using method the Rhodamin B Test Kit type II series Fast Test with category limit sensitive of 10 mg/l. Based on the results of the research that has been done can be concluded that 12 samples of food school children do not detection contain synthetic dye substances Rhodamin B through qualitative test in the laboratory department of Nutrition Poltekkes Kemenkes Denpasar. Keywords: School children's snacks, Rhodamin B